Clozapine prescribing in COVID-19 positive medical inpatients: a case series. (September 2020) - Butler, Matthew; Bano, Felicity; Calcia, Marilia; McMullen, Isabel; Sin Fai Lam, Chun Chiang; Smith, Laura Jane; Taylor, David; Gee, Siobhan
There is both uncertainty regarding the safety of clozapine in COVID-19 patients owing to limited published data and a lack of consensus on continuing clozapine in patients with severe respiratory infections. COVID-19 is known to induce an acute immune response which can affect haematological parameters associated with clozapine monitoring, and systemic infection may reduce clozapine clearance. Clozapine, which has been associated with worse outcomes in some pneumonias, may in theory worsen outcomes in COVID-19. Despite these concerns, there are some data to indicate it is safe to continue clozapine in COVID-19 infection. In this retrospective case series, we describe our experiences of clozapine prescribing and disease progression of eight SARS-CoV-2 positive patients on medical wards in a major London teaching hospital. In four cases clozapine was stopped during the hospital admission. A COVID-19 pneumonia developed in four patients: three of these required intensive care unit admission for an average of 34 days. At the time of writing, three patients had died (two directly from COVID-19 pneumonia), two remained in general hospital wards, two were recovering in the community and one had been transferred to an inpatient psychiatric hospital. Follow-up length varied but in each case was not more than 104 days. Delirium was the most common adverse neuropsychiatric event, and in one case a relapse of psychosis occurred after cessation of clozapine. This retrospective case series illustrates the safe use of clozapine during COVID-19 infection. Our experiences suggest that consideration should be made to continuing clozapine even in those most unwell with COVID-19. We also identify areas which require larger scale hypothesis-testing research.